Experience and performance of In Vivo Monitoring Laboratory of NIRP in 2017 thyroid measurement intercomparison. (February 2021) - Peng, Xuan; Zhang, Jianfeng; Ha, Wi-Ho; Kurihara, Osamu; Yang, Baolu; Tuo, Fei
Abstract: Determination of the 131 I activity in the thyroid of exposed people or workers is one of the major concerns that needs to be addressed following a nuclear or radiological emergency. International intercomparison exercises on bioassay measurements are one of the effective methods to improve the capability and quality of internal dose assessment. In 2017, Working Group 1 (Internal Dosimetry) of the Asian Radiation Dosimetry Group (ARADOS) organized an intercomparison exercise on the thyroid measurement, aiming at enhancing and coordinating the radiation dosimetry capabilities of Asian countries. This paper describes the measurement experience and results of In Vivo Monitoring Laboratory of NIRP in the 2017 intercomparison exercise, which can provide technical reference for laboratories that have not yet participated in such thyroid measurement intercomparsion. It covers technical aspects such as calibration, measurement and data processing. The results presented in this intercomparison are within an acceptable range of performance criteria on the bioassay measurements. In addition, further research work considered in the field of thyroid measurement is described in the discussion section. Highlights: The Asian Radiation Dosimetry Group (ARADOS) organized an intercomparison exercise on the thyroid measurement in 2017. The measurement experience and results of In Vivo Monitoring Laboratory of NIRP were described. A total of 8 laboratories from 3 Asian countries have participated in the exercise and the final results were presented. Intercomparison exercise enables determination of the accuracy of measurements and facilitates harmonization of methods.